PHYSICAL ACTIVITY AS DETERMINANT OF SATISFACTION WITH LIFE AMONG CADET FOOTBALL PLAYERS (Sport - nauka i praksa, 2026)
The aim of this transversal research was to examine the possibility of predicting the variables of physical activities, and quality of life in interaction with health, physical self-concept, and physical functioning in the context of explaining the criteria of satisfaction with life in cadet football players. The pertinent sample consisted of 160 participants (M age = 15.74; SD = 1.49). The Satisfaction with Life Scale – SWLS, the International Physical Activity Questionnaire – IPAQ-S, the Physical Self-Description Questionnaire – PSDQ, and the Short Form-36 Health Survey (SF-36) were used to collect data. The findings of the hierarchical regression analysis showed that significant predictors – body mass index, physical exercise, as a segment of body image, and physical functioning predict 20% of the variance of satisfaction with life (p ≤ .05). This suggests that the perception of satisfaction with life in adolescents is more relevant for engaging in physical activities than the level of their physical activities. Also, the variables such as body mass index, physical exercise, along with self-concept of physical appearance and physical functioning are important mediators in explaining the construct of satisfaction with life, so they can be guidelines for identifying the perceived level of this dependent variable in the adolescent sport population in the Republic of Serbia. Theoretical contributions and practical implications are interpreted in accordance with the correlational and multiple linear regression findings of previous empirical studies.
Keywords: adolescence; football players; physical self-concept; health status